Collected papers on environmental effects and their control in plant propagation and transplant production (Chiba, Japan, 1999)
This volume consists of three general section: journal papers, review and papers published in conference proceedings, and abstracts published during 1996-1999. All articles published during 1986-1995 were compiled in a separate edition, entitled Environmental control in micropropagation about environmental effects and their control in plant propagation and transplant production.
Keywords: Agriculture,Plant propagation,Transplant production,Nhân giống cây trồng,Môi trường; environmental aspects